The metal resources (METRO) model: A dynamic partial equilibrium model for metal markets applied to rare earth elements - Frank Pothen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper presents the METal ResOurces (METRO) model, a partial equilibrium model tailored for metal markets. It allows for a disaggregated representation of the mining sector and endogenous investment in extractive capacities. It can be calibrated to a large number of metal markets. Rare Earth Elements are the first group of metals for which the model is implemented. A new dataset on Rare Earth mines is compiled to calibrate it. First results on key developments of Rare Earth markets are presented. Extensive sensitivity analyses indicate their robustness.
urn:nbn:de:bsz:180-madoc-353660
Keywords: F17; Q31; Q37; 330; Partial Equilibrium Model; Metals; Rare Earths; Exhaustible Resources